Effects of probiotic administration on leptin levels in neonatal calves - Deniz Alic Ural; Songul Erdogan; Hasan Erdogan; Kerem Ural (Universitas Airlangga, 2026)
This study aimed to evaluate the effects of probiotic supplementation on serum leptin levels in neonatal Holstein calves over a 28-day period. Neonatal calves were allocated into three groups: probiotic administered from birth (Group 1), probiotic administered from the third day after birth when feeding with milk commenced (Group 2), and a non-probiotic control group. Leptin levels were measured on days 0, 14, and 28. A significant decrease (P = 0.013) in leptin levels was observed in Group 2 on the 14th day compared to the Control group. Conversely, a significant increase (P = 0.017) in leptin levels was detected in Group 1 on the 28th day compared to the Control group. Changes in body weight over time were not statistically significant (P > 0.05) across the groups. No significant association between leptin levels and body weight was observed at the end of the intervention. These findings indicate that probiotic supplementation, regardless of the timing of initiation after birth, does not have a substantial impact on serum leptin levels during the neonatal period in Holstein calves. Further research with larger sample sizes and consideration of additional factors influencing leptin levels is warranted.